LCA studies comparing biodiesel synthesized by conventional and supercritical methanol methods - Kiwjaroun, C.; Tubtimdee, C.; Piumsomboon, P.
Biodiesel is one of the candidates for alternative fuels since it is renewable, sustainable and produced from domestic or non-food crop resources with less detrimental environmental impact. There are several different approaches to the production process. In this paper a new production method, the supercritical methanol process, was investigated and its environmental performance was compared with the conventional alkali-catalyzed process using LCA as a tool. The supercritical process is technically a simpler production process and offers the advantages of higher yields and the production of less environmentally damaging wastes. However, it still generates a significantly higher environmental load since the methanol recovery unit requires a large amount of energy.
Keywords: BIODIESEL; SUPERCRITICAL METHANOL; ALKALI-CATALYZED; RENEWABLE ENERGY; LIFE CYCLE ASSESSMENT